Origin and Distribution of PAHs in Ambient Particulate Samples at High Mountain Region in Southern China - Peng-hui Li; Yan Wang; Yu-hua Li; Hong-li Li; Xianliang Yi (Advances in Meteorology)
To understand the deposition and transport of PAHs in southern China, a measurement campaign was conducted at a high-elevation site (the summit of Mount Heng, 1269 m A.S.L.) from April 4 to May 31, 2009, and a total of 39 total suspended particulate samples were collected for measurement of PAH concentrations. The observed particulate-bound PAHs concentrations ranged from 1.63 to 29.83 ng/m3, with a mean concentration of 6.03 ng/m3. BbF, FLA, and PYR were the predominant compounds. Good correlations were found between individual PAHs and meteorological parameters such as atmospheric pressure, relative humidity, and ambient temperature. The backward trajectory analysis suggested that particulate samples measured at the Mount Heng region were predominantly associated with the air masses from southern China, while the air masses transported over northern and northwestern China had relative higher PAHs concentrations. Based on the diagnostic ratios and factor analysis, vehicular emission, coal combustion, industry emission, and unburned fossil fuels were suggested to be the PAHs sources at Mount Heng site. However, the reactivity and degradation of individual PAHs could influence the results of PAH source profiles, which deserves further investigations in the future.